Cost-Effectiveness of the US Food and Drug Administration Added Sugar Labeling Policy for Improving Diet and Health. Issue 23 (4th June 2019) - Huang, Yue; Kypridemos, Chris; Liu, Junxiu; Lee, Yujin; Pearson-Stuttard, Jonathan; Collins, Brendan; Bandosz, Piotr; Capewell, Simon; Whitsel, Laurie; Wilde, Parke; Mozaffarian, Dariush; O'Flaherty, Martin; et al.
Abstract : Background: Excess added sugars, particularly from sugar-sweetened beverages, are a major risk factor for cardiometabolic diseases including cardiovascular disease and type 2 diabetes mellitus. In 2016, the US Food and Drug Administration mandated the labeling of added sugar content on all packaged foods and beverages. Yet, the potential health impacts and cost-effectiveness of this policy remain unclear. Methods: A validated microsimulation model (US IMPACT Food Policy model) was used to estimate cardiovascular disease and type 2 diabetes mellitus cases averted, quality-adjusted life-years, policy costs, health care, informal care, and lost productivity (health-related) savings and cost-effectiveness of 2 policy scenarios: (1) implementation of the US Food and Drug Administration added sugar labeling policy (sugar label), and (2) further accounting for corresponding industry reformulation (sugar label+reformulation). The model used nationally representative demographic and dietary intake data from the National Health and Nutrition Examination Survey, disease data from the Centers for Disease Control and Prevention Wonder Database, policy effects and diet-disease effects from meta-analyses, and policy and health-related costs from established sources. Probabilistic sensitivity analysis accounted for model parameter uncertainties and population heterogeneity. Results: Between 2018 and 2037, the sugar label would prevent 354 400 cardiovascular disease (95% uncertainty interval, 167 000–673 500) and 599 300 (302 400–957 400) diabetes mellitus cases, gain 727 000 (401 300–1 138 000) quality-adjusted life-years, and save 31 billion (15.7–54.5) in net healthcare costs or 61.9 billion (33.1–103.3) societal costs (incorporating reduced lost productivity and informal care costs). For the sugar label+reformulation scenario, corresponding gains were 708 800 (369 200–1 252 000) cardiovascular disease cases, 1.2 million (0.7–1.7) diabetes mellitus cases, 1.3 million (0.8–1.9) quality-adjusted life-years, and 57.6 billion (31.9–92.4) and 113.2 billion (67.3–175.2), respectively. Both scenarios were estimated with >80% probability to be cost saving by 2023. Conclusions: Implementing the US Food and Drug Administration added sugar labeling policy could generate substantial health gains and cost savings for the US population. Abstract : Supplemental Digital Content is available in the text.